Analisis Pengalaman Pengguna Dengan Menggunakan Mixed-Methods Approach Studi Pada Website Coppamagz - Arsy Baiq Shazkya; Retno Indah Rokhmawati; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Current development of news website have many different kinds of interest, for example sports, education, tourism to one that provide news from the entertainment industry in South Korea, such as Coppamagz.This research devine to know K-pop fans user experience using Mixed-Method Approach which has several stages to be done, that is observation to 5 experimental participants who are surfing on the Coppamagz website using Morae Software, and then participants will fill questionnaire of User Engagement Scale (UES), Cognitive Absoprtion Scale (CAS), System Usability Sacale (SUS) and then do an interview. The analysis is done by using standard deviation. The result is UES show opinions of participants who agreed (no significant difference) when selecting answer from UES questionnaire statement. From CAS questionnaire analysis shows of different experimental participants (significant differences) when selecting the answer from CAS questionnaire statement. For System Usability Scale (SUS) get SUS score 73 it means Coppamagz web interface included in Acceptable category. Keywords: Mixed-Methods Approach, user experience, User Engagement Scale (UES), Cognitive Absoprtion Scale (CAS), System Usability Scale (SUS)